1994
DOI: 10.1007/bf02599144
|View full text |Cite
|
Sign up to set email alerts
|

Deciphering the physician note

Abstract: Objective information about legibility of physician handwriting is scant. This retrospective chart review compared handwritten general medicine clinic chart notes from internal medicine faculty and housestaff with their typed counterparts. The written counterparts took 11 seconds (46%) longer to read and 5 seconds (11%) longer to answer comprehension questions. The authors' comprehension measure (developed specifically for ambulatory clinic notes) was only slightly higher for typed notes. The legibility of phy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

1997
1997
2021
2021

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 4 publications
0
4
0
Order By: Relevance
“…3). 3 The strings that result from the natural language generation are transferred automatically to a document template in Microsoft Word 97 (Microsoft, Redmond, Wash., USA) which is printed for incorporation into the paper chart.…”
Section: Natural Language Generationmentioning
confidence: 99%
“…3). 3 The strings that result from the natural language generation are transferred automatically to a document template in Microsoft Word 97 (Microsoft, Redmond, Wash., USA) which is printed for incorporation into the paper chart.…”
Section: Natural Language Generationmentioning
confidence: 99%
“…The originator may understand what has been written, but difficulties can arise when other parties are involved. Only a few studies, however, have been reported on the legibility of medical documents and these largely about prescriptions [1][2][3][4][5][6][7] . We therefore decided to examine the legibility of case histories written on admission of patients to our hospital.…”
Section: Introductionmentioning
confidence: 99%
“…16,17 Further, the legibility of physicians' writing is better than its reputation. [18][19] Finally, the problem of ambiguous medication names and doses can be ameliorated by Joint Commission on Accreditation of Healthcare Organization ( JCAHO) regulations that will banish certain abbreviations and prescription writing conventions. 20 Ash and colleagues raise a host of similar issues related to the ability of rigid computer systems to tame and serve the enormously complex and time-critical processes that churn within health care institutions.…”
mentioning
confidence: 99%